PENDEKATAN DYNAMIC EQUIVALENCE DALAM PENGGUNAAN CHANT HOHO SUKU NIAS: SEBUAH UPAYA KONTEKSTUALISASI IBADAH - Wau, Novelman; Lim, Budianto (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2024)
Over the centuries, churches in the East and West have integrated various cultural elements into liturgy, a process known as inculturation or contextualization. In Indonesia, this is evident in ethnic worship practices. However, churches in Indonesia face challenges in this process due to historical and theological factors. The first challenge is related to the influence of Western mission institutions, making it difficult to break away from Western liturgical forms. The second challenge pertains to the issue of syncretism, leading to the rejection of local cultural elements in worship. Although it is recognized that the Gospel and worship are related to the cultural context, the process of inculturation in Indonesia remains spontaneous and experimental. Cultural elements often appear as mere ornaments, without being integrated into worship. The main issue lies in how to contextualize liturgical elements, rooted in the problem of dichotomous thinking, which makes it difficult to strengthen congregational identity while preserving local culture. To address this, the author proposes analyzing the contextualization of worship with a focus on the practice of singing. Using the dynamic equivalence method, this study aims to provide a framework for incorporating the Nias chant hoho into Christian worship in a thoughtful manner. This method can offer valuable insights for other churches that wish to effectively integrate local culture into their worship practices. The author focuses this article on the specific aspect of the chant hoho, which is a Nias oral tradition that can be manifested in Christian worship as congregational singing.